Exploring the Influence of Work-Family Balance and Burnout on Working Mothers' Character-Building Efforts in a Post-Pandemic World - Evi Muafiah; Neng Eri Sofiana; Maulida Nurhidayati (Islamic Guidance and Counseling Journal, 2023)
Even though the pandemic has ended, working mothers face challenges in achieving work-family balance so that children's character education goes well. This paper looks at the effect of Work-Family Balance (WFB) and burnout on working mothers in carrying out character education for children after the COVID-19 pandemic. The method used is a quantitative method with a survey design. Data was collected from distributing questionnaires on the Google form filled in by female lecturers at the Islamic University in Indonesia. The findings of this study indicate that there is an effect of WFB and burnout on post-pandemic children's character education. Female lecturers at Islamic universities can be categorized as working mothers who can achieve WFB and educate their children well so there are no born-outs. This research shows that even as working mothers, lecturers at an Islamic university can carry out their role in children's education well.